Direct assessment of emotional well-being from children with severe motor and communication impairment: a systematic review. (4th July 2022) - Noyek, Samantha; Vowles, Caryn; Batorowicz, Beata; Davies, Claire; Fayed, Nora
Abstract: Purpose: Explore methods used in peer-reviewed literature for obtaining self-expression of well-being information from children with severe motor and communication impairment (SMCI). Materials and methods: A comprehensive search was conducted on 22 August 2019 through academic databases: CINAHL; Embase; MEDLINE; PsycINFO; InSpec; Compendex. Search strategies were informed by keywords under the following areas: (1) population: children with SMCI, (2) assessment methods: alternative to natural speech, paper and pencil report or standardized keyboard use (e.g., eye gaze) and (3) target information: well-being (e.g., quality of life). Studies were excluded if they focused on individuals over 25-years old, exclusively autism or typically developing children. Results: Non-duplicate studies of 10, 986 were screened; 49 studies met inclusion criteria. Most studies used high-tech methods of self-expression in a single context ( n = 17). Familiar partners play a significant role in self-expression; 18 studies required a familiar partner for children with SMCI to self-express. Thirty-five studies involved children self-expressing to solely adults, in comparison to 14 studies which involved peers. Conclusion: Findings highlight the advancement of high-tech communication devices restricted to application in single contexts. Familiar partner knowledge of children with SMCI has the potential to be shared with others (e.g., respite care providers), enhancing both caregiver and child well-being. Future research that would enhance the literature could explore the assessment of emotional well-being for application in various contexts using multimodal methods. Opportunities for children with SMCI to express their emotional well-being can further influence the understanding and enhancement of participation, social connections, and experiences. IMPLICATIONS FOR REHABILITATION: Use of lower tech methods of self-expression to obtain information directly from children with severe motor and communication impairment (SMCI) remain more feasible in home and school contexts. By utilizing familiar partners' experiences and knowledge of the child, respite care providers, novel support workers, and others involved in the lives of children with SMCI can become further informed. Current high-tech methods for obtaining the emotional expressions of children with SMCI may benefit from incorporating multimodal approaches including lower tech methods, to be feasibly applied in real world contexts where well-being takes place. Further research on this topic is imperative to enable children with SMCI to self-express their emotional well-being which can enhance participation, activities, social connections, and experiences.